Prevalence of Extracranial Carotid Artery Stenosis in Acute Stroke Patients in a Tertiary Care Hospital (The Planet, 2023)
Background: Extracranial carotid artery stenosis, a globalcondition, is a major risk factor for ischemic stroke. Strokerisk worsens this. Objective: This study aims to evaluate theprevalence of extra cranial carotid artery stenosis in acutestroke patients in a tertiary care hospital in Bangladesh.Method: A Dhaka tertiary care hospital's Neurologydepartment studied 40 acute stroke patients from January toDecember 2022 in a cross-sectional research. Medicalrecords were examined. Results: In our study, maximumpatients (37.5%) were between 60-69 years of age groupand 57.5% were male. 70% patients were urban people.Among the male patients, highest 17 (42.50%) had ischemicstroke. Similarly, among the female patients, highest 16(40%) had ischemic stroke. 19 (47.5%) patients hadstenosis. The prevalence of hypertension was highest (60%)followed by DM (40%) among the stenosis patients. The association between HTN, DM andboth HTN & DM of stenosis patients were significant p
Keywords: Extra Cranial Carotid Artery Stenosis; Acute Stroke Patients; Tertiary care hospital